Callose homeostasis at plasmodesmata: molecular regulators and developmental relevance - De Storme, Nico; Geelen, Danny (Frontiers in Plant Science, 2014)
Plasmodesmata are membrane-lined channels that are located in the plant cell wall and that physically interconnect the cytoplasm of adjacent cells. Operating as controllable valves, plasmodesmata regulate the symplastic trafficking of micro- and macromolecules, such as endogenous proteins (transcription factors) and RNA-based signals (mRNA, siRNA, etc.), hence mediating direct cell-to-cell communication and long distance signaling. Besides this physiological role, plasmodesmatal pores also form gateways through which viral genomes can pass, largely facilitating the pernicious spread of viral infections. Plasmodesmatal trafficking is either passive (e.g. diffusion) or active and responses both to developmental and environmental stimuli. In general, plasmodesmatal conductivity is regulated by the controlled build-up of callose at the plasmodesmatal neck, largely mediated through the antagonistic action of callose synthases (CalSs) and β-1,3-glucanases, respectively. Here, in this theory and hypothesis paper, we outline the importance of callose metabolism in PD SEL aperture control, and highlight the main molecular factors involved. In addition, we also review recent findings on other proteins that regulate symplastic PD transport, both in a developmental and stress-responsive framework, and discuss on their putative role in the modulation of PD callose turn-over. Finally, we also hypothesize on the role of structural sterols in the regulation of (PD) callose deposition and outline putative mechanisms by which this regulation may occur.